2003
DOI: 10.1100/tsw.2003.57
|View full text |Cite
|
Sign up to set email alerts
|

Psychoactive Drugs and Quality of Life

Abstract: Our study showed that over half the Danish population had used illegal psychotropic drugs. The most commonly used was cannabis (marijuana) though experience of this drug appeared not to co-vary with QOL to any significant extent. Cocaine, amphetamine, and psilocybin had been used by 1.2 to 3.3% of the population and this varied with QOL to a clear albeit small extent. LSD has been used by 1.2% of the population and the users had a QOL score 10% lower than those who had never used psychotropic drugs. The group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
2
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 14 publications
0
39
2
2
Order By: Relevance
“…Other authors have also demonstrated a negative effect of psychotropic drug use on QoL (Stein et al 1998;Ventegodt and Merrick 2003), but it remains unclear whether this can be attributed to the drug use itself or to the negative life events that may have induced drug use. Drug users' scores for physical health are similar to other populations with chronic problems, but their mental health scores are usually much lower.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors have also demonstrated a negative effect of psychotropic drug use on QoL (Stein et al 1998;Ventegodt and Merrick 2003), but it remains unclear whether this can be attributed to the drug use itself or to the negative life events that may have induced drug use. Drug users' scores for physical health are similar to other populations with chronic problems, but their mental health scores are usually much lower.…”
Section: Introductionmentioning
confidence: 99%
“…Injection Drug User Quality of Life (IDUQoL), Quality of Life Interview (QOLI), SF-36) have been used to measure the concept of QoL among drug and alcohol users (Ventegodt and Merrick 2003). The theoretical basis of most instruments for measuring quality of life in this population is often weak or non-existent and the psychometric properties can be poor (Taillefer et al 2003).…”
Section: Measuring Qol Among Substance Abusersmentioning
confidence: 99%
“…The use was connected to a small but significant reduction in quality of life. The study did not address the question whether the drug use was the result of a non-optimal quality of life (most likely), or resulted in a reduced quality of life (less likely) (Ventegodt and Merrick, 2003).…”
Section: The Habit Of Consuming Hallucinogenic Mushroomsmentioning
confidence: 99%
“…In February 1993, Ventegodt and Merrick (2003) investigated by questionnaire the connection between use of psychoactive drugs and quality of life in a representative sample of the Danish population. Among 2 460 persons aged 18 to 88 years, randomly selected from the Danish Central Register, and 7 222 person from the Copenhagen Perinatal Birth Cohort 1959-61 (31-33 years old), 61% and 64% respectively, reported their use of ten different psychotropic drugs and quality of life.…”
Section: The Habit Of Consuming Hallucinogenic Mushroomsmentioning
confidence: 99%
“…The chronic use of drugs that cause euphoria or changes in consciousness may lead to reduced QL 2 . The chronic use of cocaine or crack, in addition to higher mortality, leads to reduction in life expectancy, and several socioeconomic effects due to higher rates of hospitalization, underemployment, unemployment, and numerous other impairments such as personal suffering, isolation, stigma, and familial disengagement 2 .…”
Section: Chronic Sleep Disorders May Impair Quality Of Life (Ql)mentioning
confidence: 99%